The legal consequences of sovereign insolvency – a review of creditor litigation in Germany following the Greek debt restructuring. Issue 3 (June 2017) - Grund, Sebastian
This article analyses three seminal instances of bondholder litigation before German municipal courts following the Greek sovereign debt restructuring of 2012. While the haircut imposed on private bondholders led to a significant reduction of the country's debt level in 2012, thousands of German investors subsequently challenged the Greek government's decision before German courts. In this context, as this article highlights, even within a single jurisdiction, courts may hold very different views as to which debt management measures by a sovereign borrower ought to be considered 'public' legal acts – thus barring foreign bondholder suits – and which are 'commercial' legal acts, where litigation is a feasible legal avenue for disgruntled creditors to recover losses. In sum, however, German courts were reluctant to grant broad enforcement remedies to private bondholders, essentially vindicating the Greek government's strategy of rewriting local law and retrofitting so-called 'collective action clauses' to increase bondholder participation in the restructuring. Against this background, this article discusses some of the decisions' potential implications, such as the increased prospects for other crisis-stricken governments to successfully repeat a Greek-style debt restructuring as well as the future treatment of foreign and domestic-law public debt both by courts and market participants.